New oxide diluted magnetic semiconductor La0.75Ca0.25Cu0.75Mn0.25SO with independent spin and charge doping by first -principle study. (September 2019) - Chen, Haoze; Li, Linxian; Wang, Sheng; Li, Yuke; Chen, Jianye; Zhang, Li
Abstract: Here we report the first-principle study of a bulk oxide diluted magnetic semiconductor (DMS) La0.75 Ca0.25 Cu0.75 Mn0.25 SO and its parent LaCuSO. As a wide band gap p-type oxide semiconductor, LaCuSO system satisfies all the conditions forecasted theoretically to be a room temperature DMS, which is important for formation of high temperature spintronic devices. Then we compare the band gap and optical properties (such as loss function, reflectivity, absorption, the real part and the imaginary part of dieletric function among LaCuSO, (La0.75 Ca0.25 ) (Cu0.75 Mn0.25 )SO, (La0.75 Ba0.25 ) (Ag0.75 Mn0.25 )SO and (Y0.75 Sr0.25 ) (Cu0.75 Mn0.25 )SO. The results show that the band gap of LaCuSO system decreases most drastically with co-doped Ca and Mn (from 2.1eV to 1eV). As for the optical properties, both the position and intensity of the peaks changed most drastically, too. It illustrates that the energy band structure influences the optical properties.